Analisis Perancangan Sistem Panel Surya Off Grid pada Pencahayaan Lantai 3 Universitas Al-Azhar Medan: Analisis Perancangan Sistem Panel Surya Off Grid pada Pencahayaan Lantai 3 Universitas Al-Azhar Medan - teguh dane, Muhammad Teguh (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2025)
This study discusses the analysis and design of an off-grid solar panel system to support lighting needs on the 3rd floor of a university consisting of 6 rooms with a size of 9×7 meters each. The purpose of the study is to produce a design for an independent photovoltaic system that is able to meet lighting energy needs optimally. The methodology used includes measuring electrical loads, analyzing power requirements, calculating the capacity of main components, and economic analysis. The results of the study indicate that to meet the power needs of 3.22 kWh per day, a solar panel with a total capacity of 2.1 kWp, a 400 Ah/48V battery, and a 1.5 kW inverter are needed. The economic feasibility analysis of the system shows a Return on Investment (ROI) value of 5.8 years with a system life of up to 25 years. This study makes a significant contribution to efforts to implement renewable energy and reduce dependence on conventional electricity networks in higher education environments.